Adaptability Study of Hydrogen Fuel Cell Integrated Energy Systems - Haikui Jin; Jian Wang; Ying Wang; Yingjun Ruan; Yuan Gao; Fanyue Qian; Xiaoyan Xu; Chen Ju; Xun Dong (Energies)
This paper focuses on a hydrogen fuel cell power generation system integrated with photovoltaic (PV) generation, energy storage, and distribution network subsystems, conducting an economic and environmental adaptability analysis. Based on load balance, a mathematical model for the hydrogen fuel cell integrated energy system is established, and four scenarios are constructed: grid-powered, grid + fuel cell, grid + fuel cell + PV, and grid + fuel cell + PV + energy storage. The analysis results show that under the single-rate electricity pricing model, by 2030, the annual costs of Scenarios 3 and 4 are 11.46% and 12.67% lower than Scenario 1, respectively; by 2035, they are reduced by 19.32% and 20.43%, respectively. Under the two-part pricing model, by 2030, the annual costs of Scenarios 3 and 4 are 21.28% and 26.50% lower than Scenario 1, respectively; by 2035, they are reduced by 27.72% and 32.36%, respectively. These quantitative results indicate that the integration of hydrogen fuel cells with PV and energy storage systems can significantly reduce costs and promote their application and development in residential buildings.